Pemberdayaan Keluarga Ibu Postpartum Melalui Edukasi ‎Pengenalan Metode SPEOS Di Wilayah Kerja Puskesmas Sungai ‎Rengas ‎ - hidayah, Hidayah; Kawuryan, Uji; Surtikanti; Rikayati; Nuratika; Fatureisha, Nadila; Winarni, Tri; Kamisa, Yola (Indra Institute Research & Publication, 2023)
Early breastfeeding minimizes the risk of infant mortality by 45%. As many as 65% of newborns receive food other than breast milk in the first three days.. The results of a preliminary study conducted in the Sungai Rengas Health Center Work area, obtained data in May 2022, there were 605 postpartum mothers and the coverage of exclusive breastfeeding (0-6 months) was still low, namely 278 babies (36.9%) in 2021. This community service activity aims to increase the knowledge and skills of mothers about the SPEOS method as a non-pharmacological alternative in increasing breast milk production of postpartum mothers in the Sungai Rengas Health Center Working Area. The method used was health education with lecture and demonstration methods on the steps of the SPEOS method involving 5 postpartum mothers, 10 family members and 4 accompanying posyandu cadres. After health education activities and demonstrations of the SPEOS method, there was an increase in knowledge about the SPEOS method both from the cognitive and psychomotor aspects..